PENGARUH BUDAYA MUTU SEKOLAH DAN PENGGUNAAN MEDIA DIGITAL TERHADAP KEPUASAN BELAJAR SISWA DI SMK NEGERI 1 JOMBANG - Rohmatul Lailiyah; Erika Mei Budiarti (STKIP Pesisir Selatan, 2026)
This study aims to analyze the influence of school quality culture and digital mediause on students’ learning satisfaction at SMK Negeri 1 Jombang. This researchemployed a quantitative approach with a causal associative design. The sampleconsisted of 317 students selected using proportionate stratified random sampling.Data were collected through Likert-scale questionnaires and analyzed using multiplelinear regression. The findings show that school quality culture has a positive andsignificant effect on students’ learning satisfaction. Digital media use also has apositive and significant effect and appears as the more dominant predictor.Simultaneously, school quality culture and digital media use contribute 18.7% tostudents’ learning satisfaction, while the remaining percentage is influenced by otherfactors outside the research model. This study emphasizes the integrated role of schoolquality culture and digital media use in strengthening students’ learning satisfactionin vocational education. The findings indicate that learning satisfaction is not onlyshaped by disciplinary and quality-oriented school practices, but also by the school’sability to adapt digital learning media to students’ academic needs.